Evaluating the Incidence of Gastrocnemius Tendon Rupture in Broiler Chickens - Sokale, A.O.; Peebles , E.D.; Stayer, P.A.; Cummings, T.S.; Wills, R.W. (International Journal of Poultry Science, 2013)
The effect of feeding 3-nitro-4-hydroxyphenylarsonic acid (3-nitro) in broiler diets during low (May) and high (July) temperature months on the incidence of gastrocnemius tendon rupture (GTR) was evaluated in this study. All observations were made at a single processing plant during the months of May and July, 2010. The average live body weight (BW) of birds processed in May and July were 3.8 and 3.6 kg, respectively. The birds processed in May were fed 3-nitro in starter and grower diets (22 g/ton), whereas birds processed in July were fed 3-nitro in grower (34 g/ton) and finisher (22 g/ton) diets. Affected gastrocnemius tendons were classified as fibrosed and trimmables tendons, with trimmables subdivided into acute or chronic tendons. Data analysis by Poisson regression showed higher incidences of acute and fibrosed tendons in the month of May when compared to the month of July. Although GTR can be caused by pathogenic and non-pathogenic factors, in this field study a higher incidence of GTR observed in birds reared during low temperature months may be associated with a heavier live BW of the birds and the introduction of 3-nitro early (starter diet) in the grow-out period.